The Effect of Website-Based Information on Pregnant Women’s Knowledge of High-Risk Conditions and Birth Preparedness - Heny Rosiana; Mimi Ruspita; Septalia Isharyanti (Indonesian Health Issue, 2026)
Background Childbirth readiness and complication readiness are strategies to encourage the timely use of skilled maternal and infant health services. The low rate of early detection is a challenge, which is suspected to be influenced by the level of knowledge. Website media provides health information that is easily accessible anywhere and anytime. Purpose: This study aims to analyze the influence of information through websites on maternal knowledge about high risk in pregnancy and childbirth preparation. Methods: This type of research is a quantitative research using a pre-experimental approach with one group pre-post design. The population in this study is all pregnant women who are at risk in pregnancy at the Ringinarum Health Center. The study was conducted in August 2022, the number of pregnant women who are at risk is 36 people. Sampling uses the total sampling technique. Independent variables are the interventions provided, namely the provision of information about pregnancy risks and childbirth preparations submitted on the website media. The dependent variable is the knowledge of pregnant women. The analysis was carried out bivariate test using the Wilcoxon Test. Results: The results of the wilcoxon statistical test obtained a P-value of 0.000 or < 0.05 this shows that there is a significant influence of information through the website on the level of knowledge of pregnant women facing childbirth in the Ringinarum Health Center area. Conclusion: Providing education to pregnant women using website media to increase pregnant women's knowledge about high risk and childbirth preparation. It is hoped that pregnant women who experience a high risk of pregnancy can increase the knowledge that can be obtained through internet media.